2022
DOI: 10.1111/hiv.13410
|View full text |Cite
|
Sign up to set email alerts
|

Same‐dayand rapid initiation of antiretroviral therapy in people living withHIVin Asia. How far have we come?

Abstract: Human immunodeficiency virus (HIV) continues to be a major public health issue, and the effectiveness of HIV prevention, diagnosis, treatment, and care varies, particularly in the Asia-Pacific region. The rapid initiation of antiretroviral therapy (ART) is important to control the HIV epidemic and to optimize the health of people living with HIV; many guidelines now recommend ART initiation within 7 days of HIV diagnosis, with same-day initiation for people diagnosed with HIV who feel ready. Many countries in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The self-reported ART adherence in this study was found to be high, possibly owing to Taiwan’s policy for HIV, wherein individuals diagnosed with HIV are provided free access to ART under the national health insurance and the case management system, which provides support to PLWH in Taiwan [ 56 , 57 , 58 ]. Reducing the number of ART pills to a single-tablet regimen was found to improve adherence and quality of life among PLWH [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-reported ART adherence in this study was found to be high, possibly owing to Taiwan’s policy for HIV, wherein individuals diagnosed with HIV are provided free access to ART under the national health insurance and the case management system, which provides support to PLWH in Taiwan [ 56 , 57 , 58 ]. Reducing the number of ART pills to a single-tablet regimen was found to improve adherence and quality of life among PLWH [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was still a substantial proportion of respondents who had self-reported missing doses, suggesting a possible gap in HIV care. This finding suggests that continuous adherence counselling/reminding may still be warranted from a chronic disease management perspective [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Studies have shown that the availability of RTPs result in earlier linkage to care and earlier achievement of HIV viral suppression, although whether there are benefits in long-term retention in care or mortality remain unclear. 20,21 The optimal timing for early ART initiation is still being fully assessed, as there are concerns that immediate initiation of ART on the same day as the diagnosis of HIV infection may result in less engagement in care compared with rapid treatment initiated within 2 weeks of the diagnosis of HIV infection, 22 as the information and consideration of lifelong ART may be overwhelming. RTPs are more resource intensive, requiring multidisciplinary coordination and reprioritisation of clinic resources with more intensive initial support, but as we have shown, can result in earlier linkage to care, earlier initiation of ART and earlier attainment of HIV viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that a significant proportion of patients may be initiating antiretroviral therapy at a later stage of HIV disease, which can lead to increased risk of opportunistic infections and mortality (UNAIDS, 2021). Early initiation of antiretroviral therapy is crucial for achieving and maintaining good health outcomes for people living with HIV (Hung et al, 2022;Toska et al, 2023). HIV treatment guidelines recommend initiating antiretroviral therapy as soon as possible after diagnosis, regardless of CD4 count, in order to achieve viral suppression and reduce the risk of HIV transmission (Sarıgül Yıldırım et al, 2023).…”
Section: Causes Of Treatment Failurementioning
confidence: 99%